Discovery of Novel α-Aminophosphonates with Hydrazone as Potential Antiviral Agents Combined With Active Fragment and Molecular Docking - Tian, Jia; Ji, Renjing; Wang, Huan; Li, Siyu; Zhang, Guoping (Frontiers in Chemistry, 2022)
A series of novel α-aminophosphonate derivatives containing an acetyl hydrazine moiety were designed and synthesized based active fragment. Bioassay results demonstrated that title compounds possessed good activities against TMV. Among them, compounds 6a, 6g, 6i, 6j exhibited equivalent to the commercial antiviral agents Dufulin. Further structure optimization based molecular docking, compound 6k was synthesized and displayed excellent activity with values of 65.1% curative activity, 74.3% protective activity, and 94.3% inactivation activity, which were signiﬁcantly superior to the commercial antiviral agents Dufulin and Ningnanmycin. Therefore, this work indicated that new lead compounds could be developed by adopting a joint strategy with active fragment and molecular docking.